101 Dalmatians - Disney, Walt 1901-1966; Peet, Bill; Walt Disney Home Entertainment (Firm); Walt Disney Pictures (Burbank, CA Walt Disney Home Entertainment Distributed by Walt Disney Studios Home Entertainment, 2008)
Pongo and Perdita have a litter of 15 dalmatian puppies. Cruella De Vil takes a fancy to the puppies and tries to buy them from their human owners, Roger and Anita. Cruella wants to get ahold of those puppies, as well as more puppies, to make herself a lovely dalmatian skin coat. Cruella hires some thugs to kidnap the puppies and hold them at an abandoned mansion. Now Pongo and Perdita must use an animal communication system to help find all the puppies
Originally released as a motion picture in 1961
Title from container
Editors, Roy M. Brewer Jr., Donald Halliday ; music, George Bruns ; production designer, Ken Anderson
1
Keywords: Dalmatian dog -- England -- Juvenile drama; Fur garments -- Juvenile drama; Puppies -- England -- Juvenile drama; (3eGdJj ejOjG CWaGds -- (3ehGO SeYjI hHUQjIs